Finite element analysis of narrow excavation in clay - Rondo, Wilson (Nanyang Technological University, 2021)
Finite Element Analysis of narrow excavation in clay using PLAXIS2D has been carried out in this study. Most of the cases considered are narrow excavations in which the depth of the excavation is greater than the width of the excavation. Ten cases were analysed that considered the effects of the geometry of the excavation, properties of soil and types of wall. The results obtained from Finite Element Analysis includes basal heave Factor of Safety, maximum wall deflection and the maximum force on each strut. Evaluation of the numerical results of each case were carried out and comparisons made. The study indicates that longer wall embedment, shorter depth from the final excavation level to the underlying stiffer clay and larger undrained shear strength results in smaller wall deflections, lower strut forces and larger basal heave factor of safety, while larger wall stiffness decreases the wall deflection but results in larger strut forces.